2022
DOI: 10.21449/ijate.1058055
|View full text |Cite
|
Sign up to set email alerts
|

Examining Science Process Skills Tests: A Case of Turkey

Abstract: One of the main goals of science education is to make students gain science process skills. Thus, it is significant to measure whether students gain those skills or not. For this purpose, various tests have been produced and used in various studies. This study aims to examine science process skills tests which have been used in the theses produced in the field of science education from the perspectives of the originality, question types used, and the science process skills measured in the tests, and the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In addition, the quantitative research method and quasi-experimental design were particularly preferred in the thesis examined, with seventh-grade students as the study group, 40-60 people as the sample size, SPS and achievement tests as data collection tools, t-tests, and content analysis were generally preferred as data analysis methods. In the metasynthesis study of Sibic and Şeşen (2022), which includes the analysis of master's and doctoral thesis, they stated that SPS was generally measured with multiple-choice tests, and original tests were developed in very few of them. In the studies on the 5E educational model, the sample was generally chosen by convenience sampling as the sampling method, the sampling type was usually lower-secondary school students, the number of samples varies between 11-50, and the effectiveness of a method was tested as the research type, lower-secondary school science was concentrated as the research discipline, and the quasi-experimental method was prominent as a research method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the quantitative research method and quasi-experimental design were particularly preferred in the thesis examined, with seventh-grade students as the study group, 40-60 people as the sample size, SPS and achievement tests as data collection tools, t-tests, and content analysis were generally preferred as data analysis methods. In the metasynthesis study of Sibic and Şeşen (2022), which includes the analysis of master's and doctoral thesis, they stated that SPS was generally measured with multiple-choice tests, and original tests were developed in very few of them. In the studies on the 5E educational model, the sample was generally chosen by convenience sampling as the sampling method, the sampling type was usually lower-secondary school students, the number of samples varies between 11-50, and the effectiveness of a method was tested as the research type, lower-secondary school science was concentrated as the research discipline, and the quasi-experimental method was prominent as a research method.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive content analysis studies summarize the studies in the field of study and identify trends, facilitate the access of stakeholders to research data on the subject studied, provide holistic data about the studies, and offer new researchers the opportunity to see new and different studies on the relevant subject holistically and contribute to the researchers to develop different perspectives on the field to be studied (Çalık & Sözbilir, 2014;Dinçer, 2018). In related literature, there were some content analysis and meta-analysis studies examining science process skills (Çevik & Kaya, 2021;Sibic & Şeşen, 2022;Yıldırım et al 2016) and the 5E educational model (Anil & Batdi, 2015;Çakir & Güven, 2019;Küçüközer, 2016;Mukagihana et al, 2022;Saraç, 2018;Turan, 2021), but there was no such comprehensive study reported like the current study.…”
Section: Discussionmentioning
confidence: 99%